Freshwater juvenile ostracode data of sediment core PI-6 (85 ka BP) from Lake Petén Itzá, Guatemala (ICDP-2004/03) - Liseth Perez; Alexander Correa-Metrio (PANGAEA, 2021)
Ostracodes and pollen preserved in a 75.9-m-long sediment core (PI-6) recovered from Lake Petén Itzá, Guatemala were used to assess the magnitude and velocity of aquatic and terrestrial community responses during the last 85,000 years. Our juvenile ostracode data includes information on species abundances and richness, diversity index.
In: Perez, L; Correa-Metrio, A (2021): Freshwater ostracode and pollen data of sediment core PI-6 (85 ka BP) from Lake Petén Itzá, Guatemala (ICDP-2004/03) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.932006